Techniques of the world's best: Blocking with Bas - Gasse, M. (The Coach, 1998)
As a tall, relatively light and quick player, the Dutch Bas van der Goor has the best possible preconditions for the position of the central blocker. Over and above this, he excels through two abilities: He is always available and up with the situation and he shows very high intelligence for the game, which puts him in a position to react quickly and correctly in the situation and also to recognize and to react to surprising innovative moves by the opponents' offense.